Influence of users' cultural values on their perception of gamification elements - Inegbedion, Usunobun (2019)
This master’s thesis aims at studying how information system users from different cultural backgrounds perceive different gamification elements when they are deployed in information systems. An increasing amount of these applications are being embedded with gamification elements to boost use engagement and adoption. The thesis comprises a literature review from extant literature in the topic areas, theoretical frameworks to shore up the arguments set forth in the thesis and an empirical study. This topic is relevant for academics and industry practitioners. For academics, it helps broaden the conversation on gamification especially with respect to motivating users of information systems. It provides a theoretical framework to bolster the idea that gamification is more psychological than technical. It shows that by matching gamification elements to the cultural values of intended users, it is possible to use gamification more effectively. The empirical part of the study was conducted to investigate the propositions contained in the research framework. The study was conducted using qualitative methods and interview data was collected from two sets of respondents that represented two culturally distinct societies. The data was analysed and interpreted using qualitative content analysis. The study findings suggest that way information system users perceive gamification elements may be influenced by their cultural values. The results obtained are valid within the context of the study but are not generalisable due the limitations inherent in the study. The results also indicate that further research needs to be conducted in this subject area.